Two dimensional datamodeling and Chebyshev approximation of spline - Fauziahanim, Che Seman; ShahNor, Basri; Ahmad Faizal, Mohd Zain (The Institution of Engineers, Malaysia, 2011)
Link to publisher's homepage at http://www.myiem.org.my/